Isolation of glucosamine HCl from Penaeus monodon - Irsyaq, M. R. (2023)
Glucosamine is a compound of amino sugar that is found widely in the cartilage and has a very important role for health and joint flexibility. Glucosamine is generally produced by the hydrolysis of the exoskeletons of marine animals, one of the types of tiger prawns. In the tiger prawn shells contain chitin and chitosan compounds that can be derivatives further into glucosamine HCl. This study aimed to isolate and characterize the content of glucosamine HCl by hydrolysis of chitin and chitosan from the tiger prawns shells. Glucosamine HCl was hydrolyzed chemically using concentrated hydrochloric acid. Characterization glucosamine HCl has done by Fourier Transform Infra Red (FT-IR) spectrophotometry. Glucosamine HCl standard was used as a comparison to calculated match factor (MF). The determination of glucosamine level was performed by UV-Vis spectrophotometry with using glucosamine HCl standard as comparison. The results of the qualitative analysis showed a content of glucosamine HCl in tiger prawn shells either hydrolyzed from chitin and chitosan. It was characterized by the spectrum appears at wave number 1032cm-¹, 1537cm-¹, 3292cm-¹ for chitosan and 1032cm-¹, 1539cm-¹, 3294cm-¹ for chitin that each showed their vibration ether, CH₂ and amine group (NH). MF price of chitin and chitosan is 916.66 and 976.74, which shows that the resulting spectra are identical. The results of the quantitative analysis showed that the levels of glucosamine in chitin and chitosan 698.41 and 1,119.31 mg/g, respectively. Thus the level of glucosamine HCl in chitosan is higher than in chitin.